CuS-Based Nanostructures as Catalysts for Organic Pollutants Photodegradation - Isac Luminita; Cazan Cristina; Andronic Luminita; Enesca Alexandru (CATALYSTS, 2022)
The direct or indirect discharge of toxic and non-biodegradable organic pollutants into water represents a huge threat that affects human health and the environment. Therefore, the treatment of wastewater, using sustainable technologies, is absolutely necessary for reusability. Photocatalysis is considered one of the most innovative advanced techniques used for pollutant removal from wastewater, due to its high efficiency, ease of process, low-cost, and the environmentally friendly secondary compounds that occur. The key of photocatalysis technology is the careful selection of catalysts, usually semiconductor materials with high absorption capacity for solar light, and conductivity for photogenerated charge carriers. Among copper sulfides, CuS (covellite), a semiconductor with different morphologies and bandgap values, is recognized as an important photocatalyst used for the removal of organic pollutants (dyes, pesticides, pharmaceutics etc.) from wastewater. This review deals with recent developments in organic pollutant photodegradation, using as catalysts various CuS nanostructures, consisting of CuS NPs, CuS QDs, and heterojunctions (CuS/ carbon-based materials, CuS/organic semiconductor, CuS/metal oxide). The effects of different synthesis parameters (Cu:S molar ratios, surfactant concentration etc.) and properties (particle size, morphology, bandgap energy, and surface properties) on the photocatalytic performance of CuS-based catalysts for the degradation of various organic pollutants are extensively discussed.
Keywords: CuS nanostructuresheterojunctionsphotocatalysisorganic pollutantswastewater treatment